1988
DOI: 10.1111/j.1471-4159.1988.tb02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Kainic Acid Inhibits the Synaptosomal Plasma Membrane Glutamate Carrier and Allows Glutamate Leakage from the Cytoplasm but Does Not Affect Glutamate Exocytosis

Abstract: Kainate inhibits the exchange of D-aspartate into guinea-pig cerebrocortical synaptosomes. Kainate inhibits the Ca2+-independent efflux of endogenous glutamate in the presence of a trapping system for the released amino acid but potentiates a Ca2+-independent net efflux of endogenous and labelled glutamate and aspartate in the absence of the trap. Dihydrokainate has a similar effect. No discrepancy is seen between the release of endogenous and exogenously accumulated amino acid. These results are consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 18 publications
3
27
2
Order By: Relevance
“…However, there is also evidence that KAinduced blockade of Glu/Asp uptake can be a primary event in producing an increase in extracellular Glu and Asp (Lakshamanan et al, 1974;McGeer et al, 1978;Johnston et al, 1979;Krespan and Padmanaban, 1982;Pastuszko et al, 1984). Along these lines, one recent report in cerebrocortical synaptosomes presented evidence for a slow leak of Glu or Asp and showed that KA could potentiate this Caz+-independent net efflux of Glu and Asp apparently by inhibiting reuptake; in that system, KA did not affect Caz+-dependent synaptic release of endogenous Glu (Pocock et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence that KAinduced blockade of Glu/Asp uptake can be a primary event in producing an increase in extracellular Glu and Asp (Lakshamanan et al, 1974;McGeer et al, 1978;Johnston et al, 1979;Krespan and Padmanaban, 1982;Pastuszko et al, 1984). Along these lines, one recent report in cerebrocortical synaptosomes presented evidence for a slow leak of Glu or Asp and showed that KA could potentiate this Caz+-independent net efflux of Glu and Asp apparently by inhibiting reuptake; in that system, KA did not affect Caz+-dependent synaptic release of endogenous Glu (Pocock et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supportive to our observations that the NMDA-induced glutamate accumulation in HI cells was 50% higher than in shamoperated cells. The augmentation of NMDA-induced glutamate accumulation in HI cells can be attributed to the increase in NO production, as indicated by the cGMP formation, although blockade of uptake mechanism may also cause increase in extracellular glutamate accumulation, as done by KA (38). In the current study, NMDA-and KA-induced glutamate accumulation seems to occur by different mechanisms, because HI insults only augmented NMDA-induced glutamate accumulation and L-NMMA could block NMDA-induced but not KAinduced glutamate increases.…”
Section: Resultsmentioning
confidence: 99%
“…A number of inhibitors of the acidic amino acid transporter have been described, including cis-1 -aminocyclobutane-1,3-dicarboxylic acid (Fletcher et al, 1991), homocysteic acid (Griffiths et al, 1989) kainate and dihydrokainate (Ferkany and Coyle, 1986;Pocock et al, 1988). Some diversity of the presynaptic transporter is indicated by the failure of dihydrokainate to inhibit uptake into cerebellar synaptosomes (Ferkany and Coyle, 1986).…”
Section: The Plasma Membrane Acidic Amino Acid Transportermentioning
confidence: 99%